Employee engagement, employee satisfaction, and employee performance: evidence from an indonesian manufacturing company - Iman Sidik Nusannas; Mohd Effandi Yusoff; Patoni Patoni; Yunita Dewi Anggraeni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
Employee performance is a critical issue in manufacturing companies facing production and quality pressures. PT Chang Shin Indonesia Factory Cikampek has experienced declining production output, indicating the need to examine factors influencing employee performance. This study aims to analyze the partial and simultaneous effects of employee engagement and job satisfaction on employee performance among production employees. A quantitative associative design was employed using purposive non-probability sampling. Ninety-seven employees were selected from a population of 2,650 workers. Data were collected through a five-point Likert scale questionnaire adapted from validated previous studies. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS 25. The results show that employee engagement positively and significantly affects employee performance (β = 0.332; p = 0.001), while job satisfaction also has a positive and significant effect (β = 0.194; p = 0.002). Simultaneously, both variables significantly explain employee performance (F = 94.195; p < 0.001) with a contribution of 67%. Although limited to one manufacturing company, the findings suggest that improving employee engagement and job satisfaction can strengthen organizational performance and productivity.